Penanganan Kerusakan Jalan dengan Menggunakan Metode Pavement Condition Index - Michel Kasaf; Taufik Taufik; Jetno Harja (Yayasan Literasi Sains Indonesia, 2023)
Highways are one of the land transportation infrastructures that are very important in aspects of human activity, so that road conditions are expected to provide a sense of security and comfort for users of highway infrastructure. However, along with the increasing population in the Medan City area, the need for transportation facilities has also increased, causing a decrease in the quality of the highways which has an impact on road damage caused by roads that are burdened with high volumes of traffic repeatedly. In this study, each type of damage was measured directly in the field and analyzed using the Pavement Condition Index method and the Bina Marga method as an alternative for damage management. Based on the results of this study, the level of damage to the flexible pavement that occurred on Jalan Willem Iskandar, was that there were 7 types of damage, namely crocodile skin cracks, longitudinal cracks, transverse cracks, patches, holes, subsidence, and overturns. The overall average pavement condition index (PCI) value on the Williem Iskandar road is 64.08% with good conditions so that an alternative repair that is appropriate to the damaged conditions is to carry out maintenance per unit segment with reference to the Directorate General of Highways Standard Repair Method.